2021
DOI: 10.1080/08869634.2021.1883364
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep quality, depression, anxiety and stress levels, and temporomandibular joint disorders among Turkish dental students during the COVID-19 pandemic

Abstract: Objective: This study aimed to examine the association between sleep quality, depression, anxiety and stress levels, and the frequency of temporomandibular disorders in a sample of Turkish dental students during the COVID-19 pandemic. Methods: The current cross-sectional study was conducted with 699 dental university students during the COVID-19 pandemic. Fonseca Anamnestic Index (FAI), Pittsburgh Sleep Quality Index (PSQI), and Depression Anxiety Stress Scale-21 (DASS-21) were used in the present study. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 31 publications
(32 reference statements)
7
38
1
4
Order By: Relevance
“…A study carried out on 641 dental surgeons found TMD in 24.3% of the participants, sleep bruxism in 58%, and awake bruxism in 53.8% [101]. The incidence of TMD reported by a study carried out on 699 dental university students during the COVID-19 pandemic was of 77.5%, accompanied by impaired sleep quality, depression, anxiety, and stress [102]. Another study, based on 113 questionnaires filled out by dental students, also reported that the social isolation and stress due to the COVID-19 pandemic had led to increase symptoms of TMD, anxiety, and depression [103].…”
Section: Temporomandibular Disorders Associated With Covid-19 Pandemicmentioning
confidence: 98%
“…A study carried out on 641 dental surgeons found TMD in 24.3% of the participants, sleep bruxism in 58%, and awake bruxism in 53.8% [101]. The incidence of TMD reported by a study carried out on 699 dental university students during the COVID-19 pandemic was of 77.5%, accompanied by impaired sleep quality, depression, anxiety, and stress [102]. Another study, based on 113 questionnaires filled out by dental students, also reported that the social isolation and stress due to the COVID-19 pandemic had led to increase symptoms of TMD, anxiety, and depression [103].…”
Section: Temporomandibular Disorders Associated With Covid-19 Pandemicmentioning
confidence: 98%
“…Moreover, Gaş et al (22) reported a worse quality of sleep in dental students during COVID-19 pandemic, accompanied by symptoms of anxiety, depression and temporomandibular joint disorders.…”
Section: Related Findingsmentioning
confidence: 99%
“…Another effect of confinement among students from different parts of the world, who were also affected by restrictions on freedom of movement, was a worsening of sleep [7][8][9]. Among the most common problems were that people went to sleep later, woke up later, and also spent more time in bed [7], which did not always translate into more sleep, especially because of the reversal of daytime and night-time activities [8]. Despite this, a proportion of people reported sleeping more hours than before confinement [9], which did not result in better sleep quality.…”
Section: Introductionmentioning
confidence: 99%